Perceptions of the impact of the pandemic on teaching practices in Chile and Peru - Andrada, Pablo (2022)
This paper is part of the international EduCovid19 project that seeks to describe teachers’ perceptions of the impact of COVID-19 on their practices, as well as those of their students. In this context, this article focuses on making comparisons of teachers’ perceptions on different variables and projecting their consequences on their teaching careers. A sample (N=541) of Chilean and Peruvian teachers of all educational levels participated in the study through a virtual structured questionnaire. The results show inequalities in the teaching practices of both countries based on significant differences linked to gender inequality, socioeconomic gaps, and the academic degree of the educators.